How Indian agriculture should change after COVID-19 - Kumar, Anjani; Padhee, Arabinda K.; Kumar, Shalander (Springer, 2020)
The COVID-19 crisis has exposed the vulnerability of India’s Agri food system and accentuated the need for agricultural market reforms and digital solutions to connect farmers to markets, to create safety nets and ensure reasonable working conditions, and to decentralize Agri food systems to make them more resilient.